Design and synthesis of a novel 1H-pyrrolo[3, 2-b]pyridine-3-carboxamide derivative as an orally available ACC1 inhibitor. Issue 12 (15th June 2019) - Mizojiri, Ryo; Nii, Noriyuki; Asano, Moriteru; Sasaki, Masako; Satoh, Yoshihiko; Yamamoto, Yukiko; Sumi, Hiroyuki; Maezaki, Hironobu
Graphical abstract: Abstract: We initiated our structure-activity relationship (SAR) studies for novel ACC1 inhibitors from1a as a lead compound. Our initial SAR studies of 1 H -Pyrrolo[3, 2- b ]pyridine-3-carboxamide scaffold revealed the participation of HBD and HBA for ACC1 inhibitory potency and identified 1-methyl-1 H -pyrrolo[3, 2- b ]pyridine-3-carboxamide derivative1c as a potent ACC1 inhibitor. Although compound1c had physicochemical and pharmacokinetic (PK) issues, we investigated the 1 H -pyrrolo[3, 2- b ]pyridine core scaffold to address these issues. Accordingly, this led us to discover a novel 1-isopropyl-1 H -pyrrolo[3, 2- b ]pyridine-3-carboxamide derivative1k as a promising ACC1 inhibitor, which showed potent ACC1 inhibition as well as sufficient cellular potency. Since compound1k displayed favorable bioavailability in mouse cassette dosing PK study, we conducted in vivo Pharmacodynamics (PD) studies of this compound. Oral administration of1k significantly reduced the concentration of malonyl-CoA in HCT-116 xenograft tumors at a dose of 100 mg/kg. Accordingly, our novel series of potent ACC1 inhibitors represent useful orally-available research tools, as well as potential therapeutic agents for cancer and fatty acid related diseases.